Effects of a blend of chestnut and quebracho tannins on gut health and performance of broiler chickens - Redondo, Enzo Alejandro; Redondo, Leandro Martin; Bruzzone, Octavio Augusto; Diaz Carrasco, Juan Maria; Cabral, Claudio; Garces, Victorino M.; Liñeiro, Maximo M.; Fernandez Miyakawa, Mariano Enrique (Plos ONE, 2022)
Antimicrobial restrictions prompted the search for cost and biologically effective alternatives to replace antimicrobial growth promoters (AGPs) in food-producing animals. In addition, the efficacy of this alternatives needs to be contrasted in field/commercial trials under different challenge conditions. However only a few studies describing the impact of tannins or others AGP-alternatives in commercial poultry production conditions are actually available. The aim of the present work is to study how the inclusion of a blend of chestnut and quebracho tannins can affect broiler productive performance and health under commercial conditions. Three experiments with different approaches were conducted: (1) a trial comparing the effects of both additives (tannins vs AGP) on different commercial farms at the same time; (2) the follow-up of one farm during an entire productive year; and (3) an experimental trial using a C. perfringens challenge model in broiler chickens. Although productive results from field trials were similar among treatments, evaluations of gut health indicators showed improvements in the tannins treated flocks. Frequency and severity of intestinal gross lesions were reduced in jejunum (42% vs 23%; p<0.05–1.37 vs. 0.73; p<0.01, respectively) and ileum (25% vs. 10%; p<0.0.5–1.05 vs. 0.58; p<0.01) in tannins treated birds. Results from 16S studies, show that cecal microbiota diversity was not differentially affected by AGPs or tannins, but changes in the relative abundance of certain taxa were described, including Lactobacillus and Bifidobacterium groups. Results from experimental C. perfringens necrotic enteritis showed that tannins treated birds had reduced incidence of gross lesions in jejunum (43.75 vs. 74.19%; p<0.01) and ileum (18.75% vs. 45.16%; p<0.05) compared with control. These results suggest that AGPs can be replaced by tannins feed additives, and contribute in the implementation of antimicrobial-free programs in broilers without affecting health or performance.